The Essential Role of Wetland Restoration Practitioners in the Science-Policy-Practice Process - Clare, Shari; Creed, Irena F. (Frontiers in Ecology and Evolution, 2022)
We conducted a “living laboratory” study using a holistic transdisciplinary approach to demonstrate how new scientific tools and policy instruments could be mobilized to achieve wetland restoration goals. Our living laboratory was situated on the prairie pothole landscape in the province of Alberta, Canada, where policies require the replacement of lost wetland habitat. We created tools to map ditch-drained wetlands and to measure their functions in terms of hydrological health, water quality improvement, and ecological health to optimize targeting of wetland restoration sites. We also tested new policy instruments to incentivize private landowners to restore ditch-drained wetlands. However, we arguably failed in the implementation of the restoration program due to barriers that severely limited landowner participation, resulting in only a small number of wetlands being restored. Despite strength in science and a profound understanding of the policy, on-the-ground restoration work was stalled due to the interactive effects of environmental, social, economic, and political barriers. We discovered that despite our focus on overcoming the science-policy gap, it is the practice realm that requires more attention from both scientists and policy makers engaged in wetland restoration activities. Generally, the tools we developed were irrelevant because of complex interactions between actors and barriers within the policy, governance, and site-specific contexts that limited the use and application of the tools. Our living laboratory highlights the risks of engaging in use-inspired research without having a clear understanding of the actors and the interacting contexts that influence their behaviour, motivations, and risk tolerance. Informed by our experiences, we offer key considerations for better engagement of practitioners in the design and implementation of wetland restoration programs.